2007
DOI: 10.1021/ac7016234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MALDI to ESI on a Triple Quadrupole Platform for Pharmacokinetic Analyses

Abstract: This present work describes the systematic experimental comparison of electrospray ionization (ESI) and matrix-assisted laser desorption ionization (MALDI) for pharmacokinetic (PK) analysis of two drug candidates from rat plasma using single reaction monitoring (SRM) on a triple quadrupole mass spectrometer. The electrospray assay is an established method using a fast liquid chromatography (LC) separation of the sample extracts prior to mass spectrometry analysis. The novel MALDI assays measured the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 20 publications
(31 reference statements)
0
45
0
Order By: Relevance
“…Thus, in MALDI-MS, smaller volumes of samples can be used for analysis, smaller amounts of the samples are consumed during analysis, but higher efficiencies are obtained. Application of MALDI-triple quadrupole MS has shown that the intrinsic differences between MALDI-MS and LC-MS described above approximately cancel, and in practice therefore, the limits of quantification obtained by MALDI-MS and ESI-MS are approximately comparable (Volmer et al, 2007).…”
Section: Sample Consumption and Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in MALDI-MS, smaller volumes of samples can be used for analysis, smaller amounts of the samples are consumed during analysis, but higher efficiencies are obtained. Application of MALDI-triple quadrupole MS has shown that the intrinsic differences between MALDI-MS and LC-MS described above approximately cancel, and in practice therefore, the limits of quantification obtained by MALDI-MS and ESI-MS are approximately comparable (Volmer et al, 2007).…”
Section: Sample Consumption and Sensitivitymentioning
confidence: 99%
“…To obtain good sensitivities, the deposited matrix was re-crystallized with water vapor; this recrystallization procedure did not result in loss of spatial information. Volmer et al (2007) compared MALDI-triple quadrupole MS and LC-MS for the plasma pharmacokinetic analysis of two drug candidates that were administered to rats. Chemical analogs were used as internal standards, and plasma samples (125 mL) SMALL-MOLECULE MALDI & were prepared with SPE.…”
Section: A Quantitative Analysis Of Drugsmentioning
confidence: 99%
“…As well, silver nanoparticles were applied to a wide variety of biological molecules of different structures [7]. On the other hand, numerous SALDI materials have not shown the same universal applicability for diverse chemical structures as seen for established MALDI matrices [8][9][10] and often work only for specific compound classes.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated previously that MALDI-QqQ-MS technology has a great usability and is a versatile tool in the determination of concentrations (extra-and intracellular) of small molecules such as antiretroviral drugs (protease inhibitors), [14,15] anticancer drugs [13] but also other types of drugs [16 -18] and as screening tool in enzyme kinetic studies. [19] In a study by Volmer et al [20] the MALDI-QqQ-MS technology demonstrated equal performances compared with LC-QqQ-MS/MS instrumentation applying electrospray ionization (ESI) as ionization source when applied in pharmacokinetic studies. Previously, Notari et al [21,22] demonstrated that MALDI-TOF could be applied for the determination of low concentrations of antiretroviral drugs in plasma samples although concentrations of the antiretroviral drugs were not determined by isotope dilution mass spectrometry but by means of internal standard quantification.…”
Section: Introductionmentioning
confidence: 99%